2018
DOI: 10.1261/rna.069542.118
|View full text |Cite
|
Sign up to set email alerts
|

PinMol: Python application for designing molecular beacons for live cell imaging of endogenous mRNAs

Abstract: Molecular beacons are nucleic acid oligomers labeled with a fluorophore and a quencher that fold in a hairpin-shaped structure, which fluoresce only when bound to their target RNA. They are used for the visualization of endogenous mRNAs in live cells. Here, we report a Python program (PinMol) that designs molecular beacons best suited for live cell imaging by using structural information from secondary structures of the target RNA, predicted via energy minimization approaches. PinMol takes into account the acc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…We analyzed osk mRNA colocalization with Bru1-GFP in both the nurse cells’ cytoplasm and the ooplasm at mid stages after nurse cell microinjections with five different osk -specific molecular beacons (Fig. 1B) (Bratu et al 2003; Bayer et al 2018). Using the object-based image analysis software Icy (de Chaumont et al 2012), we found that 57±3% (n=5) of osk -containing particles associated with Bru1-GFP in the nurse cells, and 43±4% (n=6) in the oocyte (Figs 1B, S1B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We analyzed osk mRNA colocalization with Bru1-GFP in both the nurse cells’ cytoplasm and the ooplasm at mid stages after nurse cell microinjections with five different osk -specific molecular beacons (Fig. 1B) (Bratu et al 2003; Bayer et al 2018). Using the object-based image analysis software Icy (de Chaumont et al 2012), we found that 57±3% (n=5) of osk -containing particles associated with Bru1-GFP in the nurse cells, and 43±4% (n=6) in the oocyte (Figs 1B, S1B).…”
Section: Resultsmentioning
confidence: 99%
“…Egg chambers were microinjected with a solution containing a cocktail of five osk -specific molecular beacons at a concentration of 200 ng/µl of each probe. Molecular beacons were designed, synthesized, labeled and purified as we previously described (Supplemental_Methods_S2) (Bayer et al, 2018; Bratu et al, 2003). Imaging was initiated within seconds after microinjection, and data acquisition was performed at room temperature on a LeicaDMI-4000B inverted microscope (Leica Microsystems, Buffalo Groove, IL) mounted on a TMC isolation platform (Technical Manufacturing Corporation, Peabody, MA), with a Yokogawa CSU10 spinning disc head and Hamamatsu C9100–13 ImagEM EMCCD camera.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A new tool for the computational generation of RNA molecular beacons has been developed by Bayer et al 48 called PinMol. This aids with complex molecular beacon designs of up to 26 nucleotides and at least 18 nucleotides, energetically optimized through free energy optimization approaches.…”
Section: ■ Computational Methods For Fret Studiesmentioning
confidence: 99%
“…To date, accurate prediction of the structure of an RNA as well as its variations with space and time within the native cellular environment has been a formidable challenge. For simplicity, selection of potential target RNA regions has conveniently been achieved based on structures predicted by computational algorithms ( Zuker, 2003 ; Bayer et al., 2019 ). However, such algorithms could only provide somewhat reliable predictions and are particularly not accurate if the RNA of interest is greater than 400 nucleotides in length ( Reeder et al., 2006 ).…”
Section: Target Selectionmentioning
confidence: 99%